A new score based on the PEGASUS-TIMI 54 criteria for risk stratification of patients with acute myocardial infarction. (1st March 2019) - Cosentino, Nicola; Campodonico, Jeness; Faggiano, Pompilio; De Metrio, Monica; Rubino, Mara; Milazzo, Valentina; Sbolli, Marco; Perego, Carlotta; Provini, Martino; Bonomi, Alice; Veglia, Fabrizio; Bartorelli, Antonio L.; et al.
Abstract: Background: Acute myocardial infarction (AMI) patients are at increased risk of death and recurrent ischemic events. We aimed to elaborate a risk score, based on the PEGASUS-TIMI 54 criteria, to predict mortality and non-fatal AMI in AMI patients. Methods: We retrospectively analyzed two prospectively collected AMI cohorts. We calculated a cut-off for the developed score and investigated its 1-year prognostic power in the derivation cohort ( n = 1257). We externally validated our score in 913 AMI patients with a longer follow-up. Results: In the derivation cohort, the area under the curve of the score for the primary endpoint (1-year death and non-fatal AMI) was 0.70 (95% CI 0.65–0.76; P < 0.0001) and a cut-off of 6 was identified. The primary endpoint incidence in patients with a score above and below the cut-off was 12% and 3% ( P < 0.001) in the derivation cohort and 16% and 6% in the validation cohort ( P < 0.001). At multivariate analysis, the HR for the primary endpoint associated with a score ≥ 6 was 4.45 ( P < 0.0001) in the derivation cohort and 2.86 ( P < 0.0001) in the validation cohort. One-year major bleeding rate was low (<0.2% overall) and similar between risk groups. The prognostic performance of the score cut-off persisted beyond the first year after AMI in the validation cohort, maintaining a similar risk for death and non-fatal AMI (HR 3) at every following year. Conclusions: Our score, based on the PEGASUS-TIMI 54 criteria, may identify AMI patients at high risk of recurrent ischemic events, who might benefit from thorough preventive strategies. Highlights: Patients with AMI are at risk of death and recurrent ischemic events after discharge, particularly in the first year. The risk of death and recurrent AMI after AMI can be predicted early by a score based on the PEGASUS-TIMI 54 criteria. Our score is a simple bedside risk assessment tool easily employable in daily clinical practice. The evaluation of our score may also support clinical decision-making with respect to a closer clinical follow-up. Our score identifies AMI patients at high ischemic risk who may derive the greatest benefit from a more intensive therapy.